A water-waste-energy nexus approach to bridge the sustainability gap in landfill-based waste management regions. (March 2021) - Mancini, G.; Luciano, A.; Bolzonella, D.; Fatone, F.; Viotti, P.; Fino, D.
Abstract: The present paper discusses issues, scenarios, new ideas and processes with the specific purpose of quantitatively evaluating the feasibility of applying industrial symbiosis (IS) to regions where Waste-to-Energy (WtE) processes are not fully utilised (e.g. many Mediterranean regions), in order to exploit the potential synergies between 1) wastewater treatment (WWT), 2) WtE and 3) Anaerobic Digestion (AD) processes in a new, holistic approach that is able to maximise the efficient use of resources, while reducing the current environmental impacts. The enormous energy that can be obtained from residual waste is partially used, through an IS-based biorefinery approach, to thermally support the AD and drying processes of organic waste and sludge, thereby allowing 100% of the increased biogas production to be upgraded to biomethane. The need to landfill can be reduced to less than 5–10%, which allows the 2035 EU target to be achieved, with relevant economic and environmental benefits. Electricity from the WtE plant is exploited to supply the utilities of the 3 main processes and in particular to lower the costs of the required tertiary WWT and wastewater pumping phases in order to make the reclaimed water cost competitive with that of conventional water resources and thus to make this marginal water resource fully sustainable. The proposed approach can be applied in numerous countries, where landfilling is still predominant, to help stakeholders favouring a cultural shift towards a more sustainable, integrated waste/wastewater management while lowering the sterile "Not In Anyone's BackYard" (NIABY) opposition to WtE plants. Graphical abstract: Image 1 Highlights: The industrial symbiosis (IS) scenario allows the 2035 EU landfill target (<10%) to be achieved. The IS based scenario increases biogas production from OF-MSW and WWTP sludge. Through the IS-based biorefinery approach, 100% of the biogas can be upgraded to biomethane. Only the IS scenario allows a positive energy balance to achieve 100% wastewater reuse. The IS approach can lead to a cultural shift in waste/wastewater management and lower the NIABY syndrome.